Corrosion Monitoring and Evaluation of Reinforced Concrete Structures Utilizing the Ultrasonic Guided Wave Technique - Dongsheng Li; Shuaifang Zhang; Wei Yang; Wenyao Zhang (International Journal of Distributed Sensor Networks)
Corrosion of reinforced concrete structures has become a major problem worldwide, leading to very high repair costs. A dearth of studies has focused on the corrosion damage evolution of reinforced concrete. In this paper, the ultrasonic guided wave (UGW) technique is adopted to monitor the reinforced concrete corrosion damage evolution process. The properties of different guide wave modes were studied by steel rebar dispersion curves of UGWs through numerical calculation. The availability and validity of the UGW testing-reinforced concrete corrosion damage is proved by corrosion experiment. The experiment shows that the first wave peak value could describe the whole process of steel rebar corrosion. As the corrosion damage level increases, the relative variation for the first UGW peak value increases first and then decreases.